2021
DOI: 10.1038/s41598-021-90503-0
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative inhibition of SNARE-mediated vesicle fusion by α-synuclein monomers and oligomers

Abstract: The primary hallmark of Parkinson's disease (PD) is the generation of Lewy bodies of which major component is α-synuclein (α-Syn). Because of increasing evidence of the fundamental roles of α-Syn oligomers in disease progression, α-Syn oligomers have become potential targets for therapeutic interventions for PD. One of the potential toxicities of α-Syn oligomers is their inhibition of SNARE-mediated vesicle fusion by specifically interacting with vesicle-SNARE protein synaptobrevin-2 (Syb2), which hampers dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Experimental evidence has indicated that proteins Rab3A [ 72 ], Rab8b, Rab11a, and Rab13 [ 82 ] promote the clearance of α-synuclein aggregates, thereby preventing α-synuclein-induced toxicity. Additionally, α-synuclein monomers and oligomers cooperatively inhibit neuronal SNARE-mediated vesicle fusion and at sub-micromolar concentrations, α-synuclein monomers increased the fusion inhibition by α-synuclein oligomers [ 83 ]. The researchers developed a model to block oligomer binding and thus reduce toxicity during vesicle fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence has indicated that proteins Rab3A [ 72 ], Rab8b, Rab11a, and Rab13 [ 82 ] promote the clearance of α-synuclein aggregates, thereby preventing α-synuclein-induced toxicity. Additionally, α-synuclein monomers and oligomers cooperatively inhibit neuronal SNARE-mediated vesicle fusion and at sub-micromolar concentrations, α-synuclein monomers increased the fusion inhibition by α-synuclein oligomers [ 83 ]. The researchers developed a model to block oligomer binding and thus reduce toxicity during vesicle fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in neuronal systems demonstrated interaction of aSyn and SNARE-complex (soluble N-ethylmaleimide-sensitive-factor attachment receptor) molecules mediating synaptic vesicle fusion and neurotransmitter release [84,85]. Here, aSyn appears to play an important role as a regulator for complex formation and SNARE-dependent vesicle fusion by promoting vesicle docking [84][85][86]. Additionally, Scott et al identified SNARE proteins that are associated with melanocytic cell membranes [87,88] and showed that melanosomes contain the SNARE accessory protein called alpha-SNAP [87,88].…”
Section: Discussionmentioning
confidence: 99%
“…Both α-syn monomers and α-syn oligomers induce the clustering of SV. The α-syn mutant T44P/A89P with reduced lipid-binding affinity reduces the clustering of SV by α-syn oligomers in vitro [167].…”
Section: In Vitro Studiesmentioning
confidence: 98%